Surfactin Facilitates Horizontal Gene Transfer in Bacillus subtilis - Danevčič, Tjaša; Dragoš, Anna; Spacapan, Mihael; Stefanic, Polonca; Dogsa, Iztok; Mandic-Mulec, Ines (Frontiers in Microbiology, 2021)
Genetic competence for the uptake and integration of extracellular DNA is a key process in horizontal gene transfer (HGT), one of the most powerful forces driving evolution of bacteria. In several species, development of genetic competence is coupled with cell lysis. Using Bacillus subtilis as a model bacterium, we studied the role of surfactin, a powerful biosurfactant and antimicrobial lipopeptide, in genetic transformation. We showed that surfactin itself promotes cell lysis, and DNA release, thereby promoting HGT. These results, therefore, provide evidence for a fundamental mechanism involved in HGT and significantly increase our understanding of the spreading of antibiotic resistance genes and diversification of microbial communities in the environment.